2020
DOI: 10.1007/s40121-020-00380-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single-Room Care Versus Open-Bay Care on the Incidence of Bacterial Nosocomial Infections in Pre-Term Neonates: A Retrospective Cohort Study

Abstract: Introduction Nosocomial infections (NIs) are a major source of iatrogenic harm in neonatal intensive care units (NICUs). The influence of the infrastructure of NICUs on NIs is not well documented. This study aims to examine the effect of single-room units (SRU) versus open-bay units (OBU) on the incidence of NIs, including central-line-associated bloodstream infections (CLABSI), in preterm neonates. Methods All preterm neonates (< 32 weeks gestational age) admitted to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 24 publications
1
23
0
2
Order By: Relevance
“…The scientific evidence on the benefits of SRU is lacking and it remains controversial whether the available data justify the costs associated with the transformation from OBU to SRU. Apart from the independent association between single-room care and sPDA, our findings indicate that the SRU model is not associated with a reduced risk of severe morbidity and mortality in preterm neonates and are in line with our previous findings regarding the lack of association between single-room care, NEC (25 vs 17 episodes, p=0.36) and the incidence of nosocomial infection (13.68 vs 12.62 per 1000 patient-days, p=0.62) 11. We were thus unable to provide new evidence to support the theoretical benefits of single-room care.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The scientific evidence on the benefits of SRU is lacking and it remains controversial whether the available data justify the costs associated with the transformation from OBU to SRU. Apart from the independent association between single-room care and sPDA, our findings indicate that the SRU model is not associated with a reduced risk of severe morbidity and mortality in preterm neonates and are in line with our previous findings regarding the lack of association between single-room care, NEC (25 vs 17 episodes, p=0.36) and the incidence of nosocomial infection (13.68 vs 12.62 per 1000 patient-days, p=0.62) 11. We were thus unable to provide new evidence to support the theoretical benefits of single-room care.…”
Section: Discussionsupporting
confidence: 92%
“…High-grade IVH was defined as IVH grade 3 or any grade of IVH complicated by PVHI and/or PHVD. Necrotising enterocolitis and late-onset sepsis were not included as major morbidity outcomes as these outcomes have been previously reported on in relation to unit transition 11. Data for neonates who were screened for BPD and ROP following discharge from the NICU were retrieved from the hospitals to which they were discharged to.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies reported mortality (see Figure 3 and supplementary Table 2). (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Ten were before-and-after studies and the others were contemporary studies. Only one article scored less than 50% for quality and two had high quality scores.…”
Section: Mortalitymentioning
confidence: 99%
“…Twenty-three studies were found that assessed maternity and neonatal care (see Figure 3 and supplementary Table 4). (10,11,15,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) Most (n=14) were before-and after studies and the remainder were contemporaneous studies. Three studies were low quality and only one had a highquality score.…”
Section: Maternity and Neonatal Carementioning
confidence: 99%